2011
DOI: 10.1177/1524838011426014
|View full text |Cite
|
Sign up to set email alerts
|

Women With Disabilities’ Experience With Physical and Sexual Abuse

Abstract: While studies suggest that the rate of abuse of women with disabilities is similar or higher compared to the general population, there continues to be a lack of attention to this issue. Women with disabilities are at particularly high risk of abuse, both through typical forms of violence (physical, sexual, and emotional) and those that target one's disability. In an effort to highlight the need for increased attention to this issue, this article reviews the current peer-reviewed research in this field. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(72 citation statements)
references
References 39 publications
4
67
0
1
Order By: Relevance
“…Social support can promote early and continued utilisation of services; however disabled women may lack strong support networks, particularly in the context of domestic abuse [55]. Fostering positive relationships within the community is therefore essential and improving access to maternity care cannot be achieved by addressing internal service barriers alone.…”
Section: Discussionmentioning
confidence: 99%
“…Social support can promote early and continued utilisation of services; however disabled women may lack strong support networks, particularly in the context of domestic abuse [55]. Fostering positive relationships within the community is therefore essential and improving access to maternity care cannot be achieved by addressing internal service barriers alone.…”
Section: Discussionmentioning
confidence: 99%
“…Females are said to be more resilient and goal oriented or with high accomplishment levels than males. It accepts the null hypothesis that there is no significant difference between sexes to wellbeing and males tend to be happier than females because of the experiences that may experience or experiencing by the female PWDs such as gender biases (Nosek et al, 2003) and physical and sexual abuse among PWD women (Plummer & Findley, 2012) which will never or rarely experiencing by men PWDs. It contradicts the previous study wherein it was said that men are reported that possess positive emotions and women possess negative emotions because women are more emotionally expressive than men (Simon & Nath, 2004).…”
Section: Sex Differences To Wellbeingmentioning
confidence: 92%
“…Women with disabilities also face unique risk factors for abuse, including physical and social isolation; difficulty identifying abuse; dependence on abusive partners for assistance with daily needs; and general vulnerability related to disability, such as physical difficulty escaping abusive environments (Plummer & Findley, 2012). Social messages regarding the asexuality and undesirability of women with disabilities as intimate partners denigrates self-esteem, which is associated with IPV .…”
Section: Background: Ipv Disability and Trauma-informed Practicementioning
confidence: 99%